MIBG avidity correlates with clinical features, tumor biology, and outcomes in neuroblastoma: A report from the Children's Oncology Group. Issue 11 (6th April 2017) - DuBois, Steven G.; Mody, Rajen; Naranjo, Arlene; Van Ryn, Collin; Russ, Douglas; Oldridge, Derek; Kreissman, Susan; Baker, David L.; Parisi, Marguerite; Shulkin, Barry L.; Bai, Harrison; Diskin, Sharon J.; et al.
Abstract: Background: Prior studies suggest that neuroblastomas that do not accumulate metaiodobenzylguanidine (MIBG) on diagnostic imaging (MIBG non‐avid) may have more favorable features compared with MIBG avid tumors. We compared clinical features, biologic features, and clinical outcomes between patients with MIBG nonavid and MIBG avid neuroblastoma. Procedure: Patients had metastatic high‐ or intermediate‐risk neuroblastoma and were treated on Children's Oncology Group protocols A3973 or A3961. Comparisons of clinical and biologic features according to MIBG avidity were made with chi‐squared or Fisher exact tests. Event‐free (EFS) and overall (OS) survival compared using log–rank tests and modeled using Cox models. Results: Thirty of 343 patients (8.7%) had MIBG nonavid disease. Patients with nonavid tumors were less likely to have adrenal primary tumors (34.5 vs. 57.2%; P = 0.019), bone metastases (36.7 vs. 61.7%; P = 0.008), or positive urine catecholamines (66.7 vs. 91.0%; P < 0.001) compared with patients with MIBG avid tumors. Nonavid tumors were more likely to be MYCN amplified (53.8 vs. 32.6%; P = 0.030) and had lower norepinephrine transporter expression. Patients with MIBG nonavid disease had a 5‐year EFS of 50.0% compared with 38.7% for patients with MIBG avid disease ( P = 0.028). On multivariate testing in high‐risk patients, MIBG avidity was the sole adverse prognostic factor for EFS identified (hazard ratio 1.77; 95% confidence interval 1.04–2.99; P = 0.034). Conclusions: Patients with MIBG nonavid neuroblastoma have lower rates of adrenal primary tumors, bone metastasis, and catecholamine secretion. Despite being more likely to have MYCN ‐amplified tumors, these patients have superior outcomes compared with patients with MIBG avid disease.